Penerapan Media Pembelajaran Audio Visual Untuk Meningkatkan Minat Siswa ADHD Pada Mata Pembelajaran PAI - Anita Risgiani Darmawan; Asnan Nurul Habib; Misbakhul Munir; Siti Fatimah; Muna Fauziah (IAINU Kebumen, 2023)
Audio-visual learning media is one way to support increasing the learning interest of students with special needs ADHD at school. In this study, the method used to observe this increase was Classroom Action Research which consisted of 4 stages, namely planning, implementing, observing, and reflecting. Researchers conducted observations, interviews, and documentation as data collection techniques with the subject of ADHD students at SDN 1 Donosari, Sruweng, Kebumen. The analysis technique used is the Miles and Huberman model. The conclusion from this study is that the audio-visual media used in PAI learning is proven to increase interest in learning in students with ADHD.